INVESTIGATING THE PHILOSOPHICAL FOUNDATION OF AN ESP COURSEBOOK ENGLISH FOR ACCOUNTING - Luluk Iswati (Universitas Bandar Lampung, 2022)
Textbooks play an essential role in the teaching of ESP (English for Specific Purposes), especially in EFL (English as a Foreign Language) settings. Finding out the philosophical foundation of a commercial textbook can be a basis of whether or not that textbook is suitable for a particular learning context. Hence, this study aims to describe and analyze the philosophical foundation of an English for Specific Purpose (ESP) coursebook entitled ‘English for Accounting’ published by Oxford University Press, and to reveal the inferred intent of the book. This study employs a qualitative design with a content-analysis approach, in which data are described verbally. The data making was done by describing and analyzing the textbook using Littlejohn’s adapted model (2011) consisting of describing the book, analyzing the contents, and making inference. The findings show that the philosophical foundations of the textbook are eclectic, as the book employs the principles of progressivism, critical pedagogy, and reconstructivism. Regarding the intent, the book is written in order to facilitate learners to use spoken and written English for communication in various accounting business settings.